Poverty, income inequality and living standards in Ireland - Roantree, Barra; Doorley, Karina (ESRI and Community Foundation Ireland, 2023)
This report is the third from an ESRI research programme funded by Community Foundation Ireland, which seeks to address gaps in our knowledge and understanding of poverty, income inequality and living standards in Ireland. It builds on the previous reports which have found that while Ireland has experienced strong and progressive – if volatile – income growth over the past three decades both before and after accounting for housing costs, levels of income poverty and material deprivation have remained consistently high for certain groups (notably lone parents and those in working-age households where no one is in paid work). This year’s report finds the following in relation to the evolution and distribution of material living standards in Ireland
PUBLISHED
Keywords: Inclusive Society; POVERTY; income inequality